Experiment Analysis of Combustion Performance in Pulse Jet Engine. (November 2016) - Min, Liu; Ling, Yu; Wen-xiang, Cai
Abstract: Experimental research of a valve pulse-jet engine can provide theoretical support and experimental reference for the development of the engine, which provides practical fundament for the study of the operating characteristics and performance improvement of the small jet engine. An air breathing engine experimental bench including fuel supply system, a test collection system, ignition system, TR-PIV test system had been designed and built for experiment research. And a series of experimental studies on the valve type pulse-jet engine were carried out. The start-up characteristics of the engine in the intake port and combustion chamber under the fuel supply mode of the oil pump were studied. The characteristics of the engine including wall temperature, the concentration of the combustion products, the gas temperature and the pulse pressure were measured by the infrared thermal imaging system, the flue gas analyser and other equipment. The influence of fuel flow on the above parameters was studied.